2016
DOI: 10.3748/wjg.v22.i40.8892
|View full text |Cite
|
Sign up to set email alerts
|

Indications and surgical options for small bowel, large bowel and perianal Crohn's disease

Abstract: Despite advancements in medical therapy of Crohn’s disease (CD), majority of patients with CD will eventually require surgical intervention, with at least a third of patients requiring multiple surgeries. It is important to understand the role and timing of surgery, with the goals of therapy to reduce the need for surgery without increasing the odds of emergency surgery and its associated morbidity, as well as to limit surgical recurrence and avoid intestinal failure. The profile of CD patients requiring surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 121 publications
2
32
0
2
Order By: Relevance
“…This is consistent with previous observations by Cerqueira et al, who also reported that risk factors for surgery comprised disease at young age, terminal ileal involvement, and stenotic or stenotic-penetrating behavior [31]. The majority of Crohn surgeries are performed due to stenoses, followed by complications of penetrating Crohn's disease and others, such as therapy failure, gastrointestinal bleeding, a toxic megacolon, or neoplasia [32].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous observations by Cerqueira et al, who also reported that risk factors for surgery comprised disease at young age, terminal ileal involvement, and stenotic or stenotic-penetrating behavior [31]. The majority of Crohn surgeries are performed due to stenoses, followed by complications of penetrating Crohn's disease and others, such as therapy failure, gastrointestinal bleeding, a toxic megacolon, or neoplasia [32].…”
Section: Discussionsupporting
confidence: 91%
“…4,5 Surgery will be needed in more than 70% of patients with CD within their lifetime to correct a severe complication such as intestinal obstruction, perforation, fistula and abscess. 3,[6][7][8][9] Despite of surgery, the rates of postoperative recurrence are high. Endoscopic recurrence by the third postoperative year is…”
Section: Introductionmentioning
confidence: 99%
“…Overall, less than 20 to 27% remained symptom free with bowel continuity restored. 20,21 In our experience, patients with refractory Crohn's colitis managed by diverting ileostomy have shown a dismal salvage rate, ultimately requiring total proctocolectomy and permanent ileostomy.…”
Section: Crohn's Colitismentioning
confidence: 96%